2009
DOI: 10.1007/s10558-009-9063-6
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Recruitment Strategy During Cardiopulmonary Bypass Does Not Improve Postoperative Gas Exchange and Lung Function

Abstract: Pulmonary dysfunction with impairment of lung function and oxygenation is one of the most serious problems in the early postoperative period after cardiac surgery. In this study we investigated the effect of alveolar recruitment strategy during cardiopulmonary bypass on postoperative gas exchange and lung function. This prospective randomized study included 32 patients undergoing elective myocardial revascularization with cardiopulmonary bypass. In 16 patients 5 cm H(2)O of positive end-expiratory pressure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
5
0
4
Order By: Relevance
“…For example, studies in multiple settings have been unable to show that temporary gains in either lung mechanics or oxygenation extend to the postoperative environment, even when the recruitment maneuver is performed shortly before extubation 7079808182. However, the benefits of recruitment maneuvers may be enhanced or prolonged by the performance of repeated maneuvers 83.…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%
“…For example, studies in multiple settings have been unable to show that temporary gains in either lung mechanics or oxygenation extend to the postoperative environment, even when the recruitment maneuver is performed shortly before extubation 7079808182. However, the benefits of recruitment maneuvers may be enhanced or prolonged by the performance of repeated maneuvers 83.…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%
“…A randomized clinical trial [27] found no beneficial effects of these maneuvers during coronary artery bypass grafting (CABG), although other studies in the cardiac surgery setting reported that these maneuvers improved the respiratory function in the perioperative period, reducing atelectasis and improving the gas exchange [28][29][30]. It is mainly indicated in cases of hypoxemia due to alveolar collapse, as observed in anesthetized patients.…”
Section: Management Of Mechanical Ventilationmentioning
confidence: 99%
“…Ficou evidente que a repetição das manobras de recrutamento alveolar, além de aprimorar a troca gasosa e mecânica respiratória, mantém seus efeitos benéficos no período pós-operatório. 52,[57][58][59][60][61][62][63][64][65][66][67] Cirurgia cardíaca e torácica O desenvolvimento de atelectasias constitui a complicação mais comum no pós-operatório de cirurgia cardíaca e torácica, 8,43 sendo aproximadamente seis vezes maior do que o observado em cirurgias abdominais. 68 As alterações pulmonares associadas a esses procedimentos possuem fisiopatologia multifatorial e são resultado da combinação de diversos fatores.…”
Section: Cirurgia Em Pacientes Obesosunclassified